Kebijakan Luar Negeri Amerika Serikat Menjadikan Guatemala Sebagai Safe Third Country dalam Upaya Penanganan Arus Migrasi (2019-2020) - Cici Afriani Jamal; Reni Windiani; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
The United States is the destination country for foreign migrants from countries in Central America. This resulted in a border crisis caused by an increase in the number of asylum seekers in the United States. So this is a threat to the national security of the United States. Therefore, the United States through its policy of making an asylum cooperation agreement with Guatemala to minimize the flow of migration coming from Central America by making Guatemala a Safe Third Country, where asylum seekers will be diverted to follow the procedural process related to permitting asylum claims in Guatemala as a Safe Third Country in order to minimize the increase in the number of foreign migrants in the United States. However, Guatemala is said to have not met the standards set as a Safe Third Country because it is a country that has high levels of violence, inequality, poverty, an inappropriate system and unstable domestic conditions. However, the United States has its own reasons for establishing Guatemala as a Safe Third Country. This study uses neoclassical realism theory with an analytical tool in the form of a multilevel approach. The author collects data using the literature study method through journals/articles, books, websites, and international news. This research is explanatory which aims to reveal “Why did the United States choose to implement a Safe Third Country system policy towards Guatemala?”. The results of this study are the reason the United States set the policy, namely because it prioritizes national security by carrying out a migration policy with countries that already have previous relationships and cooperation.